The Role of CSF Transthyretin in Human Alzheimer's Disease: Offense, Defense, or not so Innocent Bystander - Joel N. Buxbaum (Journal of Integrative Neuroscience, 2023)
Transthyretin (TTR) is secreted by hepatocytes, retinal pigment epithelial cells, pancreatic α and β cells, choroid plexus epithelium, and neurons under stress. The choroid plexus product is the main transporter of the thyroid hormone thyroxine (T4) to the brain during early development. TTR is one of three relatively abundant cerebrospinal fluid (CSF) proteins (Apolipoprotein J [ApoJ] (also known as clusterin), Apolipoprotein E [ApoE], and TTR) that interact with Aβ peptides in vitro, in some instances inhibiting their aggregation and toxicity. It is now clear that clusterin functions as an extracellular, and perhaps intracellular, chaperone for many misfolded proteins and that variation in its gene (Clu) is associated with susceptibility to sporadic Alzheimer’s disease (AD). The function of ApoE in AD is not yet completely understood, although the ApoE4 allele has the strongest genetic association with the development of sporadic late onset AD. Despite in vitro and in vivo evidence of the interaction between TTR and Aβ, genomewide association studies including large numbers of sporadic Alzheimer’s disease patients have failed to show significant association between variation in the TTR gene and disease prevalence. Early clinical studies suggested an inverse relationship between CSF TTR levels and AD and the possibility of using the reduced CSF TTR concentration as a biomarker. Later, more extensive analyses indicated that CSF TTR concentrations may be increased in some patients with AD. While the observed changes in TTR may be pathogenetically or biologically interesting because of the inconsistency and lack of specificity, they offered no benefit diagnostically or prognostically either independently or when added to currently employed CSF biomarkers, i.e., decreased Aβ1–42 and increased Tau and phospho-Tau. While some clinical data suggest that increases in CSF TTR may occur early in the disease with a significant decrease late in the course, without additional, more granular data, CSF TTR changes are neither consistent nor specific enough to warrant their use as a specific AD biomarker.